Influence of wax and resin content on the properties of three-layer rubberwood particleboard - Lee, Seng Hua; Lum, Wei Chen; Antov, Petar; Can, Ahmet; Fatriasari, Widya; Chotikhun, Aujchariya (Universiti Teknologi MARA (UiTM), 2023)
In this study, the effects of resin and wax content as well as board density on the modulus of rupture (MOR) and internal bonding (IB) and thickness swelling (TS), were investigated. Three-layer particleboard was made with rubberwood particles. Different urea formaldehyde (UF) resin contents (%) were applied on the surface/core/surface layer of the particleboard, namely 10/7/10, 11/8/11 and 12/9/12. Three different dosages of wax (0, 0.5 and 1%) were added into the UF resin and blended with the rubberwood particles during particleboard fabrication. Particleboard with two densities was roduced, which are 680 kg/m3 and 750 kg/m3. The results revealed that the wax content exerted an insignificant effect on the MOR and IB of the particleboard, but it greatly improved the TS of the board. Meanwhile, resin content was observed to reduce the TS and increase the MOR of the particleboard. Particleboard with higher density had better MOR and IB. However, the TS value increased also along with increasing board density. Unfortunately, all the boards produced in this study did not meet the minimum requirement of TS value as specified in JIS A 5908, which should be lower than 12%. The optimisation study recommended that a higher wax content (1.47%) be used to achieve the targeted TS. Nevertheless, it is not viable from the economic point of view, and another option has to be considered to lower the TS of the particleboard.